2020
DOI: 10.1111/jfd.13237
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia lake virus: The story so far

Abstract: Tilapia lake virus (TiLV) is a highly contagious pathogen that has detrimental effects on tilapia farming. This virus was discovered in 2014 and has received tremendous global attention from the aquaculture sector due to its association with high fish mortalities and its strong economic impact on the tilapia aquaculture industry. Currently, TiLV has been reported in 16 countries, and this number is continuing to rise due to improved diagnostic assays and surveillance activities around the world. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 97 publications
3
85
0
Order By: Relevance
“…Tilapia tilapinevirus, aka tilapia lake virus (TiLV), was first described in farmed and wild tilapia in Israel [4] and later reported in sixteen additional countries [2,48,49]. Although the potency of TiLV has been demonstrated in various species of tilapia including Nile tilapia (Oreochromis niloticus), blue tilapia (O. aureus), and its hybrid species [4,5,15,42,50,51], there have been no reports of TiLV infection in Mozambique tilapia, which is genetically close to the Nile tilapia, a susceptible host to TiLV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tilapia tilapinevirus, aka tilapia lake virus (TiLV), was first described in farmed and wild tilapia in Israel [4] and later reported in sixteen additional countries [2,48,49]. Although the potency of TiLV has been demonstrated in various species of tilapia including Nile tilapia (Oreochromis niloticus), blue tilapia (O. aureus), and its hybrid species [4,5,15,42,50,51], there have been no reports of TiLV infection in Mozambique tilapia, which is genetically close to the Nile tilapia, a susceptible host to TiLV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Tilapia Lake Virus Disease (TiLVD) is a new disease caused by Tilapia tilapinevirus, or tilapia lake virus (TiLV), which is a linear, negative-sense single-strand RNA virus containing ten segments; it has a total genome size of 10,323 kb [1,2]. Since 2014, TiLV has been reported on four continents, North America, South America, Asia, and Africa [2][3][4]. All stages of tilapia, from fry to adult and broodstock, are susceptible to TiLV, with mortality ranging from 5% to 100% [2,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was observed that the variation of nucleotides at position 412 of the Colombian sequences showed a change at position 130 of the amino acid sequence of the protein. These changes in both nucleotides and amino acids of the TiLV strains detected within the same country were described for segments 1, 5, and 9 in the TiLV strains detected in Thailand [ 9 , 30 ].…”
Section: Discussionmentioning
confidence: 80%
“…This study demonstrated morbidity rates of 50-100% and mortality rates of 30-87% in each fish farm. The prevalence of TiLV infection is low and increases when massive mortalities are observed [ 14 , 15 , 30 ]. Results of the present study revealed 27.27% (18/66) prevalence of TiLV, indicating a more significant prevalence than that reported in Peru [ 21 ] at 14.8% (4/27) but lower than that reported in Ecuador [ 11 ], which was 63% (17/27).…”
Section: Discussionmentioning
confidence: 99%